The Influence of Sleep, Menstrual Cycles, and Training Loads on Heart Rate Variability: A Four-Year Case Study on an Elite Female Slalom Kayaker - Samo Rauter; Ajda Novak; Nina Verdel (Applied Sciences)
This study aimed to examine the influence of training load, performance, sleep, and menstrual parameters on heart rate variability (HRV) and to evaluate its potential as a predictor of sports performance. A four-year longitudinal case study was conducted on a female elite kayak athlete, involving daily monitoring of HRV, sleep quality and duration, menstrual cycles, illnesses, and acute training loads. Over this period, 1394 measurements were taken each morning immediately after waking up and before getting up. The results of four competitive seasons were analyzed using a performance index and were statistically processed with a linear mixed model. The analysis revealed a statistically significant positive association between rMSSD and both sleep quality (p < 0.001) and the follicular phase of the menstrual cycle (p = 0.003). In contrast, the training load (p = 0.94), sleep duration (p = 0.27), and illness (p > 0.05) showed no statistically significant effect on rMSSD. Additionally, neither rMSSD (p = 0.82) nor its trend (p = 0.70) were significant predictors of the performance index. Despite the lack of a statistically significant correlation between HRV and sports performance, the findings suggest that the pre-competition decrease in HRV observed in this case study may reflect anticipatory physiological changes, potentially linked to increased sympathetic activation, as suggested in the existing literature.